[tex]a + b + c = 23[/tex]
[tex]x = 9[/tex]
[tex]2013 - (53a + 53b + 53c + 10x)[/tex]
[tex] = 2013 - [53(a + b + c) + 10x][/tex]
[tex] = 2013 - (53 \times 23 + 10 \times 9)[/tex]
[tex] = 2013 - (1219 + 90)[/tex]
[tex] = 2013 - 1309[/tex]
[tex] = 704[/tex]
[tex]424 - 21x + 3a + 3b + 3c[/tex]
[tex] = 424 - 21x + 3(a + b + c)[/tex]
[tex] = 424 - 21 \times 9 + 3 \times 23[/tex]
[tex] = 424 - 189 + 69[/tex]
[tex] = 235 + 69[/tex]
[tex] = 304[/tex]
[tex]3147 - 10x - (100a + 100b + 100c)[/tex]
[tex] = 3147 - 10 x - 100(a + b + c)[/tex]
[tex] = 3147 - 10 \times 9 - 100 \times 23[/tex]
[tex] = 3147 - 90 - 2300[/tex]
[tex] = 3057 - 2300[/tex]
[tex] = 757[/tex]